Physical therapy as a promising treatment for osteoarthritis: A narrative review - Wang, Wei; Niu, Yonggang; Jia, Qingxiu (Frontiers in Physiology, 2022)
Osteoarthritis (OA) is the most prevalent joint disease and a leading cause of disability in older adults. With an ageing and increasingly obese population, OA is becoming even more prevalent than in previous decades. Evidence indicates that OA is proximately caused by the breakdown of joint tissues from mechanical loading and inflammation, but the deeper underlying mechanism of OA pathogenesis remains unclear, hindering efforts to prevent and treat this disease. Pharmacological treatments are mostly related to relieve symptoms and there is no drug for radical cure. However, compelling evidences suggest that regular practice of resistance exercise may prevent and control the development of several musculoskeletal chronic diseases including OA, which may result in improved quality of the patients. In this review, we introduced the current understanding of the mechanism and clinical treatments of OA pathogenesis. We also reviewed the recent study of physical therapy in the treatment of skeletal system disorders, especially in OA. In the end, we discussed the present challenges of physical therapy in OA treatment, as well as the privileges for promoting physical therapy in OA patients.